Discursos e iniciativas de metodistas progressistas sobre a questão agrária no Brasil (1980-1999) / Discourses and initiatives of progressive Methodists on the agrarian issue in Brazil (1980-1999) - Almeida, Vasni de (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2013)
O estudo se volta para os discursos e práticas políticas de metodistas progressistas sobre a questão agrária e desenvolvidos nos movimentos sociais de luta pela terra no Brasil, nas décadas de 1980 e 1990. Os dizeres e iniciativas sociais nessa questão se deram, entre outros, no campo da instrução religiosa e nas interlocuções entre os movimentos de trabalhadores rurais e agentes religiosos da igreja. Esse envolvimento político ocorreu sustentado no evangelismo social e nos documentos metodistas no que se refere à responsabilidade social da igreja. Abstract The study is about the political discourses and practices of progressive Methodists on the agrarian issue, developed in the social movements that struggle for land in Brazil, in the 1980s and the 1990s. The sayings and social initiatives in this matter took place, among others, in the field of religious education and in the dialogues between rural workers movements and religious agents of the church. This political involvement was sustained by the social evangelism and the Methodist documents regarding the social responsibility of the church.